Penetapan Harga Jual Barang Dagang Pada PT. X Di Surabaya - Vivi Puspita Anggraeni; Wiratna Wiratna; Achmad Daengs GS; Diana Zuhroh; Sutini Sutini; Tjandra Wasesa; Heri Toni Hendro P (Jurnal Mahasiswa Manajemen dan Akuntansi, 2023)
This study aims to determine the determination of the selling price of trade goods at PT. X and the right selling price of merchandise at PT. X. The research method used is descriptive qualitative. The types of data used in this study are qualitative and quantitative data collected by field survey techniques, literature studies, observations, documentation, and interviews. The subject of this study was PT. X, with the object under study is the determination of the selling price of trade goods at PT. X. Researchers used income statements, as well as inventory helper books from 2019 to 2021. The results of research at PT. X regarding the determination of the selling price of merchandise is still not right than what should be set by the company according to information from the company and the selling price is set with a large percentage only part of the profit expected by the company alone without calculating the operational costs that have been incurred by the company in a certain period of time for the merchandise. After the selling price is recalculated as a percentage according to information from the company, it is still unable to cover the company's operating costs which within 3 years continue to increase and are still with an operating loss position. Then the selling price is calculated and redetermined based on the new markup percentage by calculating the operating costs incurred and the amount of profit expected by the company in 3 merchandise inventories in 2019-2021, obtained net profit in 2019 of IDR 23,088,849, in 2020 of IDR 51,481,314, and in 2021 of IDR 49,104,928. Determining the right selling price in the company is expected to provide the maximum possible profit for the company and achieve company goals.